COMMUNITY FLOOD DISASTER PREPAREDNESS POLICY; A STUDY IN THE SOBO RIVERBANK AREA, BANYUWANGI - Fitriyani; Hary Priyanto; Niko Pahlevi Hentika (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Floods frequently occur along the Sobo Riverbanks in Banyuwangi District. These disasters are caused by vulnerable physical environmental conditions and human activities. Community preparedness is a crucial factor in mitigating the impact of flooding, but its implementation has not been optimal. This study aims to analyze community preparedness through a policy implementation perspective by examining implementing organizations, desired policies, target groups, and environmental factors. The study used a descriptive qualitative approach using interview, observation, and documentation techniques. The results indicate that the Regional Disaster Management Agency (BPBD) still plays a dominant role in the emergency response phase, preparedness policies are not yet fully operational, community preparedness is still reactive, and physical and socioeconomic environmental factors influence low preparedness. This study emphasizes the need for strengthening pre-disaster management, community empowerment, and integrated environmental management to improve flood preparedness.